The relationship between big five of personality traits and cyberloafing / Umi Aida Sugiman - Sugiman, Umi Aida (Faculty of Business and Management, 2019)
The aim of this study was to investigate the relationship between big five of personality traits and cyberloafing among employees in Dyson manufacturing in Johor. Big five of personality traits which are conscientiousness, agreeableness, neuroticism, openness to experience and extraversion were used as the main factor in this study. Convenience sampling was used in this research and all the questionnaire was distributed to employees in Dyson Manufacturing. Social Science Software or SPSS version 22 was used In order to interpret the data that had been collected. The findings from this study was shown that neuroticism, openness to experience and extraversion have relationship with cyberloafing meanwhile conscientiousness and agreeableness no relationship with cyberloafing.